Gas-hydrogeochemical conditions of the Bilche-Volytsia oil-gas-bearing area (Carpathian foredeep, Ukraine) - Harasymchuk, Vasyl; Medvid, Halyna; Solovey, Tatiana (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2021)
Introduction. Water-dissolved gases in exploratory oil and gas hydrogeology are the fundamental criteria of oil and gas potential. Their quantitative and qualitative characteristics allow to study the conditions of formation and preservation of the hydrocarbon deposits and to identify the perspective searching areas.The purpose of article was to determine the vertical and lateral gas-hydrogeochemical zonation of the Bilche-Volytsia oil and gas zone, to assess the role of water-dissolved gases in the formation of gas fields with the prospect of predicting new hydrocarbon deposits.The research methods base on the calculation and interpretation of the following parameters: gas saturation of water, saturation pressure, gas saturation coefficient. Graphs of dependences based on experimental studies from published scientific publications were used to determine the solubility of methane.The results of research. Nitrogen-methane composition of water-dissolved gases of the Upper Jurassic and Upper Cretaceous aquifers in combination with specific geochemical characteristics of groundwater of the north-western and central parts of the Bilche-Volytsia OGBA indicate the open hydrodynamic conditions, which, in general, are unfavourable for the formation and preservation of hydrocarbon deposits. In deep-submerged reservoirs of the south-eastern part of this area, water-dissolved gases of the Upper Jurassic and Upper Cretaceous aquifers are characterized by high contents of methane homologues.In the Upper Badenian aquifer the lateral distribution of water-dissolved methane is presented in the growth of its portions from the West and East European platforms in the direction of the sub-submerge of the Carpathians, which is due to an increase in the degree of hydrogeological closure of structures. Increased methane contents also spatially tend to transverse tectonic faults, which determines their role in the vertical migration of water-hydrocarbon mixtures.Water-dissolved gases of the highly productive Lower Sarmatian aquifer are mainly methane, occasionally nitrogen-methane. The gas saturation of the waters directly correlates with the proximity to gas deposits. Laterally, the portion of water-dissolved methane is directly correlated with TDS of water, the high values of which accordingly reflect the structures of a high degree of hydrogeological stagnation.Conclusions. The portions of water-dissolved methane increase from the West and East European platforms in the direction of the sub-submerge of the Carpathians, which is effect of higher degree of hydrogeological closure of structures. It has been established that water-dissolved methane, nitrogen and carbon dioxide have different sources of origin and different spatiotemporal mechanisms of water saturation. The hydrodynamically closed structures (favourable for the formation and preservation of hydrocarbon deposits) characterized by high relative and absolute contents of dissolved methane. Increased methane contents also spatially tend to transverse tectonic faults, which determines their role in the vertical transportation of water-hydrocarbon mixtures. Deep hydrodynamically closed aquifers of the Bilche-Volytsia OGBA often are marked by high nitrogen contents of non-air origin. Its source can be rock organic matter, bound rock nitrogen released during metamorphism, nitrogen of deep genesis.